2016
DOI: 10.1111/imr.12389
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies targeting CD38 in hematological malignancies and beyond

Abstract: Summary CD38 is a multifunctional cell surface protein that has receptor as well as enzyme functions. The protein is generally expressed at low levels on various hematological and solid tissues, while plasma cells express particularly high levels of CD38. The protein is also expressed in a subset of hematological tumors, and shows especially broad and high expression levels in plasma cell tumors such as multiple myeloma (MM). Together, this triggered the development of various therapeutic CD38 antibodies, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
187
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(205 citation statements)
references
References 159 publications
2
187
0
7
Order By: Relevance
“…The anti-CD38 monoclonal antibody daratumumab has shown a favorable safety profile and encouraging efficacy in patients with refractory multiple myeloma (25)(26)(27), and the anti-CD38 SAR650984 is being examined as a treatment for CD38 ϩ hematological malignancies, including AML (clinicaltrials.gov registration NCT01084252). Here, we have found that treatment of AML cell lines and primary AML apheresis samples with IFN␥ leads to the up-regulation of M1-related markers and of the daratumumab target CD38.…”
mentioning
confidence: 99%
“…The anti-CD38 monoclonal antibody daratumumab has shown a favorable safety profile and encouraging efficacy in patients with refractory multiple myeloma (25)(26)(27), and the anti-CD38 SAR650984 is being examined as a treatment for CD38 ϩ hematological malignancies, including AML (clinicaltrials.gov registration NCT01084252). Here, we have found that treatment of AML cell lines and primary AML apheresis samples with IFN␥ leads to the up-regulation of M1-related markers and of the daratumumab target CD38.…”
mentioning
confidence: 99%
“…59 Preclinical studies indicate that CD38 is a potential target for antibody therapy in CD38-positive hematological malignancies. 18,19 The anti-CD38 monoclonal antibody Daratumumab is approved for the treatment of multiple myeloma and is currently being assessed for CLL. Anti-CD38 monoclonal antibodies are believed to exert their antitumor activity through their Fc-dependent cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence indicates that they can modulate CD38 enzymatic activity by decreasing cADPR production, which may in turn lead to decreased Ca 21 mobilization and signaling. 18,60 Further characterization of CD38-dependent signaling, including the RasGRP2/Rap1 axis, is therefore important for the design of novel treatments for CD38 1 hematological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…39 CD38 is a 45 kDa membrane protein expressed in a number of hematological malignancies from B-lymphocyte, T-lymphocyte, and myeloid origin ( Table 1 …”
Section: Anti-cd38 Monoclonal Antibodiesmentioning
confidence: 99%